2009
DOI: 10.1111/j.1365-294x.2009.04374.x
|View full text |Cite
|
Sign up to set email alerts
|

Major histocompatibility complex heterozygote advantage and widespread bacterial infections in populations of Chinook salmon (Oncorhynchus tshawytscha)

Abstract: Despite growing evidence for parasite-mediated selection on the vertebrate major histocompatibility complex (MHC), little is known about variation in the bacterial parasite community within and among host populations or its influence on MHC evolution. In this study, we characterize variation in the parasitic bacterial community associated with Chinook salmon (Oncorhynchus tshawytscha) fry in five populations in British Columbia (BC), Canada across 2 years, and examine whether bacterial infections are a potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
110
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(115 citation statements)
references
References 72 publications
3
110
1
1
Order By: Relevance
“…For example, pathogen invasion must be prevented in all species. This has been observed in the study of MHC II molecular evolution (Surridge et al, 2008;Evans and Neff, 2009). …”
Section: Conservation Of Mdii-2 Indicates the Same Function And Similsupporting
confidence: 52%
“…For example, pathogen invasion must be prevented in all species. This has been observed in the study of MHC II molecular evolution (Surridge et al, 2008;Evans and Neff, 2009). …”
Section: Conservation Of Mdii-2 Indicates the Same Function And Similsupporting
confidence: 52%
“…Other studies of the MHC have also found higher levels of observed heterozygosity than expected, suggesting that selection for heterozygotes is occurring in many species (for example, Seddon and Baverstock, 1999;van Haeringen et al, 1999;Peters and Turner, 2008;Oliver et al, 2009;see Garrigan and Hedrick, 2003 for review). In a recent study, we have shown that MHC class II heterozygous Chinook salmon fry exhibit fewer bacterial infections that do homozygotes (Evans and Neff, 2009). Moreover, a study by Arkush et al (2002) on Chinook salmon showed that heterozygotes at the MHC class II exhibited higher survival than homozygotes when challenged with infectious haematopoietic necrosis virus (but see Langefors et al, 2001).…”
Section: Evans Et Almentioning
confidence: 95%
“…Hence, putative LA at MHC loci can be viewed as a hierarchical process with different dynamics acting on different geographical scales. Yet a similar study on chinook salmon (Oncorhynchus tshawytscha) found no evidence for any MHC alleles to confer bacterial resistance (Evans and Neff 2009). Further research is merited to discern complexities related to the role of pathogen communities in the evolution of salmonid host LA.…”
Section: Approach IImentioning
confidence: 99%